2016
DOI: 10.1016/j.infbeh.2015.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of support surface and optic flow on step-like movements in pre-crawling and crawling infants

Abstract: Step-like movements were examined in pre-crawling (n=9) and crawling (n=9) 6–13 month-old infants in the air and on a surface in response to a static pattern or optic flows that moved toward or away from the infant. Infants completed six 60-second trials. A significant interaction between locomotor status and support condition revealed that pre-crawling infants made more step-like movements in the air than on a rigid surface. In contrast, crawling infants made an equivalent number of step-like movements in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…(2023) reported that infants made more movements of the arms and legs when they supported them horizontally above an optic flow moving toward them compared to a static checkerboard pattern. Their findings, in addition to the current and previous findings, further support the hypothesis that all of the locomotor movement patterns infants express might emerge from the same neuromuscular substrate (Anderson et al., 2016; Barbu‐Roth et al., 2009, 2014, 2015; Forma et al., 2018, 2019).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…(2023) reported that infants made more movements of the arms and legs when they supported them horizontally above an optic flow moving toward them compared to a static checkerboard pattern. Their findings, in addition to the current and previous findings, further support the hypothesis that all of the locomotor movement patterns infants express might emerge from the same neuromuscular substrate (Anderson et al., 2016; Barbu‐Roth et al., 2009, 2014, 2015; Forma et al., 2018, 2019).…”
Section: Discussionsupporting
confidence: 88%
“…Barbu‐Roth and colleagues have hypothesized that kicking, stepping in the air, stepping on a surface, swimming, and crawling movements might all emerge from the same neuromuscular substrate (Anderson et al., 2016; Barbu‐Roth et al., 2009, 2014, 2015; Forma et al., 2018, 2019). Their argument built on Thelen and colleagues' earlier hypothesis that infant stepping and kicking might represent the same movements expressed in different postural contexts (e.g., Thelen et al., 1981; Thelen & Fisher, 1982; Thelen et al., 1984), with specific muscle activity patterns and movement kinematics reflecting the particular field of external forces generated by the postural context.…”
Section: Introductionmentioning
confidence: 99%
“…The potential for infants to learn new behaviors and the acquisition of early locomotor function is also important for shaping and normal maturation of sensorimotor integration and psychological development (Anderson et al, 2013(Anderson et al, , 2016(Anderson et al, , 2019. Therapy utilizing novel dynamic weight assistance technology (Prosser et al, 2012; Figure 6C) may allow practice of motor skills that children are not yet able to perform on their own (crawling, knee walking, walking, climbing, attempts to jump and falling).…”
Section: Early Interventions To Promote the Locomotor Function In Infmentioning
confidence: 99%
“…Slower contraction time of muscles (Dayanidhi et al, 2013 ), maturation of nerve conduction time (attributable to increasing fiber diameter; Eyre et al, 1991 ) and ossification of the foot skeleton (Maier, 1961 ) also affect the peripheral shaping of the locomotor output. Moreover, the influence of the supraspinal inputs on the functioning and outcome of the spinal pattern generation circuitry cannot be ruled out (Barbu-Roth et al, 2014 ; Anderson et al, 2016 ; Ritterband-Rosenbaum et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%